2011
DOI: 10.5402/2011/476158
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Animal Model for Parkinson's Disease: The Intranigral Injection of LPS Induced the Inflammatory Process along with the Selective Degeneration of Nigrostriatal Dopaminergic Neurons

Abstract: We have developed an animal model of degeneration of the nigrostriatal dopaminergic neurons, the neuronal system involved in Parkinson's disease (PD). The implication of neuroinflammation on this disease was originally established in 1988, when the presence of activated microglia in the substantia nigra (SN) of parkinsonians was reported by McGeer et al. Neuroinflammation could be involved in the progression of the disease or even has more direct implications. We injected 2 μg of the potent proinflammatory com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 181 publications
(175 reference statements)
1
26
0
Order By: Relevance
“…Indeed, increased oxidative enzymes COX1 and iNOS (Hunot et al., ; Knott et al., ) and pro‐inflammatory cytokines have been reported to be increased in human PD SN (Boka et al., ) and striatum (Nagatsu, Mogi, Ichinose, & Togari, ) and if persistent, this pro‐inflammatory response may hasten cell death. Accordingly, in rodents a robust immune activation via intracerebral injection of the bacterial membrane molecule: lipopolysaccharide (LPS) results in nigral dopaminergic cell death (Hoban et al., ; Machado et al., ).…”
Section: The Microglia Response Happens Early Due To Changes In Neuromentioning
confidence: 99%
“…Indeed, increased oxidative enzymes COX1 and iNOS (Hunot et al., ; Knott et al., ) and pro‐inflammatory cytokines have been reported to be increased in human PD SN (Boka et al., ) and striatum (Nagatsu, Mogi, Ichinose, & Togari, ) and if persistent, this pro‐inflammatory response may hasten cell death. Accordingly, in rodents a robust immune activation via intracerebral injection of the bacterial membrane molecule: lipopolysaccharide (LPS) results in nigral dopaminergic cell death (Hoban et al., ; Machado et al., ).…”
Section: The Microglia Response Happens Early Due To Changes In Neuromentioning
confidence: 99%
“…LPS, a component of the cell wall of Gram-negative bacteria can induce in ammation responds. Studies have demonstrated that the injection of LPS into the SN of rats can induce PD symptoms [27,28]. In the experiment, we found that mice injected with LPS in the SN had PD symptoms such as weight loss and motor dysfunction compared with control mice.…”
Section: Discussionmentioning
confidence: 70%
“…LPS, a component of the cell wall of Gram-negative bacteria can induce in ammation response. Studies have demonstrated that the injection of LPS into the SN of rats can induce PD symptoms [27,28]. In the experiment, we found that mice injected with LPS in the SN had PD symptoms such as weight loss and motor dysfunction compared with control mice.…”
Section: Discussionmentioning
confidence: 70%